高校用検定教科書による未知語の推測 - 八島, 等 (全国英語教育学会紀要, 2003)
The study examines success in guessing unknown words from context in the 1:40 unknown word ratio. The study also examines differences in subjects' propensity to use local and global clue types. Data are analyzed according to subjects' vocabulary size and subjects' school year - 1^, 2^, and 3^. Results show significant differences in success rates across school years. Also regardless of vocabulary size, 3^ year students' mean success rate was 60 percent or greater. Results also show that the subjects use local clues significantly more frequently than global clues. Students with a vocabulary size of 4,000 words or greater were able to guess around 65 percent of unknown words successfully regardless of their school years and regardless of the passages' distribution of global versus local clue types. I conclude that a minimum vocabulary size of 3,500 words is necessary for subjects to guess more than 60 percent of unknown words successfully.